AN AODV-based clustering and routing scheme for mobile ad hoc networks - Denko, Mieso K. (2006)
A mobile ad hoc network (MANET) is a collection of wireless mobile nodes forming a temporary network without the aid of any fixed communication infrastructure. Due to limited resources, frequent network partitions and unpredictable topological changes, proactive clustering schemes incur high overheads in this environment. In this paper, we propose an on-demand, distributed clustering algorithm for MANETs based on an Ad hoc On-demand Distance Vector (AODV) routing protocol. The use of on-demand routing protocol information for clustering reduces clustering overhead because no clusters are maintained unless they are needed. The clustering algorithm’s stability was assessed using clustering metrics such as cluster head and cluster members lifetime. Based on this clustering scheme, a cluster-based routing protocol was proposed to add scalability to the AODV routing protocol. Using simulation, a comparison was made with a pure AODV protocol. Simulation experiments show that the scheme results in stable and scalable clusters and Cluster- AODV routing introduces less overhead than the pure AODV protocol without clustering